Exploring the Arabic animation film landscape: filmmaker perspectives from seven nations - Ghanem Ayed Elhersh; M. Laeeq Khan; Haneen Khaled Alqawasmeh (Cogent Social Sciences, 2024)
This study investigates the insights of ten Arab animators who are actively involved in the production of animated content in seven Arab countries. The research endeavors to shed light on two significant domains: (i) the perspectives of animators regarding the Arabic animation sector and (ii) the numerous determinants that impact the industry’s growth. By utilizing thematic analysis to interpret the data obtained from in-depth interviews, this study reveals that Arab animators hold a pervasive sense of dissatisfaction with the current state of the industry. Notwithstanding these obstacles, the animators strive to elevate their work to an international level and offer insightful critiques of the challenges faced by the regional film and animation industries. The study delineates critical determinants influencing the Arabic animation sector, encompassing technological assistance, financial limitations, access to training and educational resources, and skilled labor. The results of this study have important ramifications for the progress of the film and media industries, especially in developing nations where these sectors encounter substantial obstacles.